[tex]4\sqrt{44} - 5\sqrt{99} +2\sqrt{11} = 4\sqrt{4*11} - 5\sqrt{9 *11} +2\sqrt{11} = 8\sqrt{11}-15\sqrt{11}+2\sqrt{11} = -5\sqrt{11}[/tex]
[tex]...=(\sqrt{7} - \sqrt{4*7} )*\sqrt{7} - (3\sqrt{10} -2\sqrt{4*10} )*\sqrt{10} = \\(\sqrt{7} - 2\sqrt{7} )*\sqrt{7} - (3\sqrt{10} -4\sqrt{10} )*\sqrt{10}=\\-\sqrt{7} *\sqrt{7} -(-\sqrt{10} )*\sqrt{10} = \\-7 + \sqrt{10} *\sqrt{10} = -7+10 = 3[/tex]
[tex]10 \sqrt{2} =20\sqrt{\frac{1}{2}}\\20\sqrt{\frac{1}{2}}=\sqrt{\frac{1}{2}*400} =\sqrt{\frac{400}{2}} = \sqrt{200} = \sqrt{2*100} = 10\sqrt{2}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1.
2.
3.
[tex]4\sqrt{44} - 5\sqrt{99} +2\sqrt{11} = 4\sqrt{4*11} - 5\sqrt{9 *11} +2\sqrt{11} = 8\sqrt{11}-15\sqrt{11}+2\sqrt{11} = -5\sqrt{11}[/tex]
[tex]...=(\sqrt{7} - \sqrt{4*7} )*\sqrt{7} - (3\sqrt{10} -2\sqrt{4*10} )*\sqrt{10} = \\(\sqrt{7} - 2\sqrt{7} )*\sqrt{7} - (3\sqrt{10} -4\sqrt{10} )*\sqrt{10}=\\-\sqrt{7} *\sqrt{7} -(-\sqrt{10} )*\sqrt{10} = \\-7 + \sqrt{10} *\sqrt{10} = -7+10 = 3[/tex]
4.
[tex]10 \sqrt{2} =20\sqrt{\frac{1}{2}}\\20\sqrt{\frac{1}{2}}=\sqrt{\frac{1}{2}*400} =\sqrt{\frac{400}{2}} = \sqrt{200} = \sqrt{2*100} = 10\sqrt{2}[/tex]
[tex]0,6\sqrt{2} > 0,3\sqrt{5}\\\\0,6\sqrt{2} = \sqrt{2*0,6^{2} } = \sqrt{2*0,36 }=\sqrt{0,72} \\\\0,3\sqrt{5} = \sqrt{5*0,09} =\sqrt{0,45}[/tex]